Applying Constructionist Principles to Online Teacher Professional Development - Ostashewski, Nathaniel; Reid, Doug; Moisey, Susan (International Review of Research in Open and Distributed Learning, 2011)
This report explores the first iteration of a teacher professional development courselet grounded in constructionist theory and activities. This online teacher professional development (oTPD) courselet provided opportunities for teachers to engage in just-in-time, ongoing TPD within a social networking site for educators. The topic of the oTPD was Robotics and Hands-on Activities in the Classroom. The courselet was designed for teachers who are interested in integrating constructionist pedagogies into their practice. Key findings of the first delivery of the oTPD courselet point to a need for flexible access, sharing of resources, and support for constructionist pedagogical activities as a PD value for participants. Findings further support the potential for an ongoing online community of practice around robotics in the classroom. The approach taken in this oTPD courselet of study continues to inform a model of oTPD delivery within a social-networking-enabled environment.